Biogeochemical properties of seawater in Lützow-Holm Bay in February 2011 during the 52nd Japanese Antarctic Research Expedition - TAKAHASHI, Kunio T.; TAKAMURA, Tomomi R.; IIDA, Takahiro; NISHIOKA, Jun; ODATE, Tsuneo (2015)
P(論文) Fig.1, 2 | http://polaris.nipr.ac.jp/~parc/pub/v003/nipr_parc_183_0003_2011.docx Table 1 | http://polaris.nipr.ac.jp/~parc/pub/v001/nipr_parc_183_0001_2011.doc Table 2 | http://polaris.nipr.ac.jp/~parc/pub/v002/nipr_parc_183_0002_2011.doc departmental bulletin paper